2010
DOI: 10.1021/es1021735
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Models for Estimating Mercury Flux from Soils

Abstract: Multiple parameters have been suggested to influence the exchange of mercury (Hg) between the atmosphere and soils. However, models applied for estimating soil Hg flux are simple and do not consider the potential synergistic and antagonist relationships between factors controlling the exchange. This study applied a two-level factorial experimental design in a gas exchange chamber (GEC) to investigate the individual and combined effects of three environmental factors (temperature, light, and soil moisture) on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 36 publications
5
51
0
1
Order By: Relevance
“…Soil types, soil moisture and Hg content in soil are also important factors influencing observed Hg 0 flux (Xu et al, 1999;Kocman and Horvat, 2010;Lin et al, 2010a). observed that rainfall and irrigation enhances soil Hg 0 emission by 1 order of magnitude.…”
Section: Air-soil Hg Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…Soil types, soil moisture and Hg content in soil are also important factors influencing observed Hg 0 flux (Xu et al, 1999;Kocman and Horvat, 2010;Lin et al, 2010a). observed that rainfall and irrigation enhances soil Hg 0 emission by 1 order of magnitude.…”
Section: Air-soil Hg Exchangementioning
confidence: 99%
“…Environmental factors interact naturally (e.g., irradiation and temperature), which can impose synergistic and antagonistic effects on forcing Hg 0 flux changes (Gustin and Stamenkovic, 2005). Figure 4 shows the individual effects and synergism between solar radiation, air tem- perature and water content on Hg 0 flux from a typical low organic content soil (∼ 1.5 wt %) (Lin et al, 2010a). The three individual factors enhance flux by 90-140 %, while two-factor synergetic effect accounts for additional 20-30 % enhancement.…”
Section: Air-soil Hg Exchangementioning
confidence: 99%
“…1). Previous researches suggested that Hg emission flux from soils was positively correlated with soil surface temperature and solar radiation especially in laboratory investigation (Kocman and Horvat, 2010;Lin et al, 2010;Choi and Holsen, 2009a); however, it was also often observed that there was no significant relationship between Hg emission flux and environmental parameters in field experiments (Stamerkovic et al, 2008;Ericksen et al, 2006). For example, a peak of Hg emission flux (58.1 ng m -2 hr -1 ) occurred from LS during early morning (around 2 am) on May 29 th when soil temperature and UV-A radiation were low; however, early morning peak was not shown on May 30th (Fig.…”
Section: Hg Exchange In Lawn Soilmentioning
confidence: 99%
“…For example, the soil temperature, redox potential, moisture content, and organic matter content significantly affect the TGM concentration in forest soils. Studies have shown that higher soil temperatures can increase atmospheric TGM fluxes (Gustin et al 1997; Choi and Holsen 2009;Lin et al 2010) and lead to higher TGM concentrations in background soils (Sigler and Lee 2006). The soil redox potential might affect soil TGM concentrations by changing the availability of electrons for oxidation-reduction reactions involving Hg(II) and GEM (Schuster 1991;Zhang and Lindberg 1999;Obrist et al 2009).…”
Section: Introductionmentioning
confidence: 99%